Rapid-response RNA-fluorescence in situ hybridization (FISH) assay platform for coronavirus antiviral high-throughput screening - Ryan Chan; Christian Shema Mugisha; Vorada Chuenchob; Stephanie A. Moquin; Ujjini H. Manjunatha; Nadine Jarrousse; Vineet D. Menachery; Xuping Xie; Erika L. Flannery; Richard T. Eastman (SLAS Discovery)
Over the past 25 years, the global community has faced challenges posed by three distinct outbreaks of coronaviruses including severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome coronavirus (MERS-CoV), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The identification of a novel alphacoronavirus canine CoV (CCoV-HuPn2018) in human patients in Malaysia underscores the potential for crossover infections to humans. The threat of the ever-evolving nature of viral infections as well as the lingering health and socioeconomic effects of the recent SARS-CoV-2 pandemic emphasize the urgent need for advanced antiviral drug screening tools that can be quickly implemented to strengthen preparedness and preventive measures against future outbreaks. Here, we present the development and validation of a novel RNA-fluorescence in situ hybridization (FISH) imaging assay as a 384-well, high-throughput rapid response platform for antiviral drug discovery. RNA-FISH is a powerful tool to visualize specific mRNA in cultured cells using a high-content imaging platform. The flexibility of RNA-FISH probe sets allows for the rapid design of viral genome-specific probes, enabling in vitro assay development to test for inhibition of viral replication by either biologic or small molecule inhibitors. Screening of 170 antiviral compounds in concentration-response demonstrates a strong correlation between the RNA-FISH assay and an immunofluorescence assay (IFA) for both human coronaviruses HCoV-OC43 and HCoV-229E. Additionally, we successfully applied this methodology in the context of CCoV strain 1–71, proving rapid development and deployment, opening new avenues for the evaluation of antiviral drugs to potential future emerging threats.